Characterization of Input Current Interharmonics in Adjustable Speed Drives - Soltani, H.; Davari, P.; Zare, Firuz; Loh, P.; Blaabjerg, F. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
This paper investigates the interharmonic generation process in the input current of double-stage adjustable speed drives (ASDs) based on voltage-source inverters and front-end diode rectifiers. The effects of the inverter output-side low order harmonics, caused by implementing the double-edge symmetrical regularly sampled space vector modulation technique, on the input current interharmonic components are presented and discussed. Particular attention is also given to the influence of the asymmetrical regularly sampled modulation technique on the drive input current interharmonics. The developed theoretical analysis predicts the drive interharmonic frequency locations with respect to the selected sampling strategies. Simulation and experimental results on a 2.5 kW ASD system verify the effectiveness of the theoretical analysis.